Analysis of Age and Gender Factors on the Incidence Rate of Cataracts in the Ophthalmology Clinic - Wijayanti, Lumastari Ajeng; Mainassy, Meillisa Carlen; Aryadi, Anggi; Pannyiwi, Rahmat; Said, Asbath; Harlina, Harlina (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Cataracts are a cause of blindness which accounts for approximately half of all blindness in the world, especially in developing countries. The mechanism of cataract formation is highly multifactorial. Loss of transparency in the nucleus and cortex of the lens of the eye can occur as a result of oxidation of membrane lipids, structural or enzymatic proteins by peroxides or free radicals induced by UV light. Other factors that can cause cataract formation are degenerative processes and diabetes mellitus). Cataract therapy is a surgical procedure by removing the cloudy lens, because no medical therapy has been proven to remove cataracts in adults. There are many methods that can be done with surgery for cataract patients. One of them is phacoemulsification, which is a cataract surgery using a small incision method. In this technique, liquefaction of the lens is made using an ultrasound probe that is inserted through an incision in the cornea or anterior sclera. This study aims to determine the relationship between age and gender with the incidence of cataracts at the Eye Polyclinic Outpatient Installation in 2022. This is a retrospective analytic study by examining data in the Recamedics Department. The data is grouped by age, sex and type of cataracts. There were 197 patients who came to the eye polyclinic in July 2022. From the results of the study, 197 people suffered from cataracts with a percentage of 88 men (45%) and 109 women (55%) and the age group that suffered the most from cataracts was the age group 53-68 years and the most common cataracts were senile cataract. Analysis of the relationship between age and gender with the incidence of cataracts in the Outpatient Installation (Poly Eyes) for the period of July 2022 obtained a value for the relationship between age and the incidence of cataracts P = 0.846 and the relationship between sex and the incidence of cataracts P = 0.01. Conclusion: In this study there is a significant relationship between gender and the incidence of cataracts and there is no relationship between age and the incidence of cataracts.